2021
DOI: 10.1007/s11356-021-14322-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of meteorological factors and Air Quality Index on the COVID-19 epidemiological characteristics: an ecological study among 210 countries

Abstract: The survival of COVID-19 in different environments may be affected by a variety of weather, pollution, and seasonal parameters. Therefore, the present study aims to conduct an ecological investigation on COVID-19 average growth rate of daily cases and deaths influenced by environmental factors (temperature, humidity, and air pollution) using a sample size of adjusted cumulative incidence of daily cases and deaths based on five 60-day periods. Research data was gathered on official websites, including informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…A wide array of meteorological factors including particulate matter, air pollution, and heat were identified as positively associated with the spread of COVID-19. Studies identified that reported on the relationship between meteorological parameters and COVID-19 spread in different regions of the world [ [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] ] are shown in Table 1 . The interplay among meteorological factors (air pollution, meteorological parameters, and climate change) ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide array of meteorological factors including particulate matter, air pollution, and heat were identified as positively associated with the spread of COVID-19. Studies identified that reported on the relationship between meteorological parameters and COVID-19 spread in different regions of the world [ [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] ] are shown in Table 1 . The interplay among meteorological factors (air pollution, meteorological parameters, and climate change) ...…”
Section: Resultsmentioning
confidence: 99%
“…Statistical analyses were conducted using R software. Decline in air quality contributed to a greater number of daily COVID-19 cases and deaths [ 76 ] Global Meteorological variables, COVID-19 infections and mortality Weather data were extracted from the NOAA database. COVID infection and death rates were obtained from World Health Organization reports.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, several meaningful cross-country conclusions can be drawn from the comparison of this paper and five relevant empirical researches. We compared five cohort studies focusing on the relationship between PM10 and dementia, all of which are from low-pollution countries such as the USA, Canada and Australia (Grande et al 2020 ; Ilango et al 2020 ; Paul et al 2019 ; Vali et al 2021 ). The results systematically indicated that in low-pollution countries, a 100 μ g/ m 3 increase in APCs was associated with a 14–32% increase in the hazard ratio of suffering dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Infectious diseases may be directly transmitted through airborne particles or pollutants (Metcalf et al., 2017). At the same time, high air pollution levels can also interfere with people's immune systems and weaken the ability of the respiratory system to remove viruses (Mohebat et al., 2021). These evidence all indicate that the level of air pollution is closely related to the spread of infectious diseases.…”
Section: Methodsmentioning
confidence: 99%